Research Gap on Oral Corrective Feedback in Second Language Acquisition Theory - Affective Filter Analysis: A Conceptual Framework - Ramdani, Amaliah; Musa, Nur Ainun; Nurchalis, Nur Fadillah; Dahlan, Suratman (Journal of Language Learning and Assessment, 2024)
Purpose Oral corrective feedback, despite its historical precedence, continues to captivate researchers' interest, driving ongoing discourse within the scholarly community. The existing body of research on this subject displays a degree of controversy, with divergent perspectives regarding its efficacy. While proponents endorse its utilization, opposing voices question its impact. This study seeks to identify research gaps within the last decade to provide a comprehensive understanding of the current state of oral corrective feedback literature.  Methodology Employing content analysis, data are extracted from pertinent documents, shedding light on the existing landscape.  Results/Findings This study suggests that while oral corrective feedback is widely used and debated in language learning, there is insufficient research addressing its potential drawbacks. It calls for further studies to fill this gap and ensure that oral corrective feedback practices effectively benefit language learners. Implications This study emphasizes the importance of future research in refining practices and ensuring positive outcomes in language education.